Drogas ilícitas en Colombia: su impacto económico, político y social - Thoumi, Francisco E.; Uribe Ramírez, Sergio; Rocha García, Ricardo (Ariel ciencia política, 1997)
"Exhaustive study analyzes how drug trade has impacted Colombia's economy, rural land purchases, rainforest colonization and deforestation, violence, international commercial and financial relations, and other key areas. The most complete and unbiased study to date"--Handbook of Latin American Studies, v. 57